2015
DOI: 10.1063/1.4907223
|View full text |Cite
|
Sign up to set email alerts
|

Note on quantitatively correct simulations of the kinetic beam-plasma instability

Abstract: A large number of model particles is shown necessary for quantitatively correct simulations of the kinetic beam-plasma instability with the clouds-in-cells method. The required number of particles scales inversely with the expected growth rate, as in the kinetic regime only a narrow interval of beam velocities is resonant with the wave.PACS numbers: 52.65. Rr, 52.35.Qz Beam-plasma interaction plays an important role in various physical phenomena such as transport of relativistic electrons in the fast igniti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…This is observed to occur by around tω pe = 9000, which is in excess of the time scale predicted by the aforementioned quasilinear theory formula (τ ql ω pe = (n b /n 0 ) −1 (v b /∆v b ) 2 ). We however, confirmed that this is a realistic relaxation time for this setup in our convergence testing, rather than being artificially hastened as a side-effect of poor computational particle counts as reported by and Lotov et al [2015]. The discrepancy is instead due to the use of the relatively dense and energetic beams which are outside of the formal applicability of the quasi-linear theory, as discussed in Section 2.…”
Section: Homogeneous Regimesupporting
confidence: 79%
“…This is observed to occur by around tω pe = 9000, which is in excess of the time scale predicted by the aforementioned quasilinear theory formula (τ ql ω pe = (n b /n 0 ) −1 (v b /∆v b ) 2 ). We however, confirmed that this is a realistic relaxation time for this setup in our convergence testing, rather than being artificially hastened as a side-effect of poor computational particle counts as reported by and Lotov et al [2015]. The discrepancy is instead due to the use of the relatively dense and energetic beams which are outside of the formal applicability of the quasi-linear theory, as discussed in Section 2.…”
Section: Homogeneous Regimesupporting
confidence: 79%
“…Umeda (2010) reported that increasing pseudoparticle numbers diminished the signal associated with harmonic emission. Under-resolved particle numbers could contribute to excessive noise on the EM dispersion curves (and be mis-interpreted as emission as per the first point) and also result in poor replication of physical time-scales as per Ratcliffe et al (2014) and Lotov et al (2015). Finally, all of the previous works consider systems with high beam-to-background density ratios (all take n b /n 0 > 1%) and are so in the strong beam regime.…”
Section: Introductionmentioning
confidence: 99%
“…As the instability time scales with the inverse of the beam-to-background density ratio (e.g., the quasilinear relaxation timescale is τ ql = (n 0 /n b ) (v b /Δv b ) 2 ω −1 pe ), direct simulation of astrophysical parameter regimes where beams are typically diffuse (n b /n 0 ≈ 10 −5 −10 −6 ) requires the simulation to run for tens-to-hundreds of thousands of electron plasma periods. Furthermore, this is compounded in that huge particle numbers are required to correctly resolve the expected quasilinear relaxation timescales with the particle-in-cell (PIC) method Lotov et al 2015). Lotov et al (2015) found empirically that for beam-plasma systems the number of pseudoparticles per cell required scales as the inverse of the fraction of (real) particles which are in resonance with the beam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations were conducted of the relativistic electron beam interacting with plasma [32]. These simulations resulted in the correct value of the two-stream instability increment.…”
Section: Introductionmentioning
confidence: 99%